Press on principles of interaction programming - Thimbleby, Harold (MIT Press, 2007)
How to understand and program interactive devices so that they are reliable and easy to use; includes wide-ranging programming insights, tools, and code.
Title from title screen.
Keywords: Computer programming.; Human-computer interaction.; elektronické knihy; electronic books